Treatment of actinic cheilitis with daylight photodynamic therapy-Clinical and histopathological evaluation - Baltazar, Isabella Lemos; Ferreira, Flávia Regina; Nascimento, Luiz Fernando Costa [UNESP]; Mandelbaum, Samuel Henrique (GN1 Sistemas e Publicacoes, 2019)
Introduction: Actinic cheilitis (AC) is a premalignant condition resulting from chronic sun exposure that affects the lower lip vermillion. Daylight Photodynamic Therapy (DL-PDT) is a new alternative to conventional therapy, being more straightforward, more accessible, and with better tolerability. Objective: To evaluate the efficacy and applicability of DL-PDT in the treatment of AC and to determine the most prevalent adverse events. Material and Methods: Experimental study, uncontrolled clinical trial type. The included patients were selected based on clinical and histopathological diagnosis of AC. Aminolevulinic acid was applied to the lower lip, and the sun exposure was conducted (3 sessions/ 2-week interval). We performed pre and post-treatment biopsies, took photographs for documentation, and filled out a default form. Results: The study included 11 patients (63.6% men); mean age 59 years, and predominance of Fitzpatrick skin phototype II (45.4%). We observed a statistically significant clinical improvement (p = 0.026), but not histologically confirmed. The adverse events were minimal (46% asymptomatic). Conclusions: The study evaluated the efficacy and applicability of DL-PDT in the treatment of AC and determined the prevalent adverse events, motivating, and supporting future studies.
Tratamento da queilite actínica com terapia fotodinâmica com a luz do dia-avaliação clínica e histopatológica
Keywords: Hyaluronic acid; Skin aging; Skin care